2014
DOI: 10.1186/1479-5876-12-151
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of IL-4 and TNFα on the induction of B7-H1 in renal cell carcinoma cells inhibiting allogeneic T cell proliferation

Abstract: BackgroundThe importance of B7-H molecules for the T cell/tumor communication and its impact on renal cell carcinoma (RCC) progression and prognosis has been recently described. Cytokine treatment of RCC has earlier been shown to be beneficial in preclinical settings, but its clinical implementation has not proven to be as effective. This might be partially explained by the yet incomplete picture of cellular alterations in tumor cells upon cytokine treatment investigated in detail in this study.MethodsRCC tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 51 publications
1
46
0
1
Order By: Relevance
“…Several secreted cytokines or growth factors were considered candidates for the secreted PD-L1 upregulation, based on previous work [25, 26, 3032], including GM-CSF, MCP-1, IL-10, IL-3, TGF-β, or TNF-α. To help identify the relevant factors, we first screened recombinant cytokines to identify those that most strongly upregulated PD-L1 expression in the bone marrow monocyte system (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several secreted cytokines or growth factors were considered candidates for the secreted PD-L1 upregulation, based on previous work [25, 26, 3032], including GM-CSF, MCP-1, IL-10, IL-3, TGF-β, or TNF-α. To help identify the relevant factors, we first screened recombinant cytokines to identify those that most strongly upregulated PD-L1 expression in the bone marrow monocyte system (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, other cytokines have been found to also upregulate PD-L1 expression. IL-4 and TNF-α were found to synergistically upregulate PD-L1 on certain human cancer cell lines [25]. In another study, monocytes were found to upregulate PD-L1 in response to IL-10 and IL-32γ, and TGF-β induced upregulation of PD-L1 expression on B cells [26].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effect of Rh2 and Rh2-M on proliferation of A549 cells was detected by MTT assay (Quandt et al., 2014 ). In logarithmic growth phase, A549 cells were digested with trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…The B7‐H1 expression is largely controlled by cytokine‐mediated regulation of promoter regions. Quandt et al reported that B7‐H1 expression and alter T‐cell responses are mediated by interleukin‐4 and necrosis factor in renal cell carcinoma (RCC; Quandt, Jasinski‐Bergner, Mueller, Schulze, & Seliger, 2014). The PD‐L1 conjugation with TGF‐β‐STAT3 may contribute to immune dysfunction and act as a potential novel target site for therapeutics (Song, Park, Nam, Choi, & Sung, 2011).…”
Section: Interaction Of Cytokines Production In Pd‐l1/pd‐1 Blockagementioning
confidence: 99%